Gallic Acid Suppresses Cardiac Hypertrophic Remodeling and Heart Failure. Issue 5 (27th December 2018) - Yan, Xiao; Zhang, Yun‐Long; Zhang, Liang; Zou, Lei‐Xin; Chen, Chen; Liu, Ying; Xia, Yun‐Long; Li, Hui‐Hua
Abstract : Scope: Gallic acid (GA) is a dietary phenolic acid found in tea, red wine, and some plants. It exhibits anti‐oxidative and anti‐inflammatory activities. Recent studies have revealed that GA has beneficial effects against several cardiovascular diseases; however, whether GA attenuates pressure‐overload‐induced cardiac hypertrophy and the underlying mechanism remains unclear. Methods and results: Primary cardiomyocyte hypertrophy is stimulated with angiotensin II (Ang II). Cardiac hypertrophic remodeling is induced in mice by transverse aortic constriction (TAC). Myocardial function is evaluated by echocardiographic and hemodynamic analyses, while cardiac tissues are analyzed by histological staining. It is observed that GA significantly decreases Ang II‐induced increases in cardiomyocyte size in vitro. Administration of GA in mice markedly improves TAC‐induced cardiac dysfunction and attenuates pathological changes, including cardiac myocyte hypertrophy, fibrosis, inflammation, and oxidative stress. Mechanistically, GA inhibits ULK1 and activates autophagy, which induces the degradation of EGFR, gp130, and calcineurin A, thereby inhibiting the downstream signaling cascades (AKT, ERK1/2, JAK2/STAT3, and NFATc1). Conclusions: The results demonstrate for the first time that GA prevents myocardial hypertrophy and dysfunction via an autophagy‐dependent mechanism. Thus, GA represents a promising therapeutic candidate for treating cardiac hypertrophy and heart failure. Abstract : Gallic acid (GA), a type of dietary phenolic acid found in tea and other plants, prevents angiotensin II‐induced cardiomyocyte hypertrophy and pressure overload‐induced myocardial dysfunction. Mechanistically, GA enhances autophagy activation which promotes degradation of epidermal growth factor receptor, glycoprotein 130 and calcineurin A resulting in inhibition of downstream signaling cascades.